2013
DOI: 10.1007/s11239-013-0957-1
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of RDW is associated with non-valvular atrial fibrillation

Abstract: Red cell distribution width (RDW) and neutrophil/lymphocyte ratio (NLR) have been found to be associated with cardiovascular diseases. Only a few trials have investigated the correlation of these parameters with postoperative atrial fibrillation (AF). However, the correlation of these parameters in non-valvular AF is still unclear. We retrospectively analyzed consecutive AF patients from medical records and included 117 non-valvular AF patients (103 paroxysmal and 14 chronic AF). All subjects underwent physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…In a population-based analysis of 25,612 persons in Norway, there was a linear association between baseline RDW and risk of myocardial infarction, with 13% increase in MI risk for every 1% increment in RDW 31 , which persisted after exclusion of patients with anemia 32 . Similarly, studies have associated RDW with the presence of coronary artery disease 33 , peripheral vascular disease 34 , and atrial fibrillation 35 . We are unaware of any prior report describing the relationship between RDW and cardiovascular disease in the context of HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…In a population-based analysis of 25,612 persons in Norway, there was a linear association between baseline RDW and risk of myocardial infarction, with 13% increase in MI risk for every 1% increment in RDW 31 , which persisted after exclusion of patients with anemia 32 . Similarly, studies have associated RDW with the presence of coronary artery disease 33 , peripheral vascular disease 34 , and atrial fibrillation 35 . We are unaware of any prior report describing the relationship between RDW and cardiovascular disease in the context of HIV infection.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, some studies in the literature did not report an association between NLR and AF occurrence [20]. Güngör et al [21] reported a correlation of RDW and CRP with rate of AF paroxysms, but NLR and other hematological parameters were not correlated with AF. On the basis of these conflicting results, Shao et al [20] carried out a meta-analysis and reported that admission NLR levels were associated with an increased risk of AF recurrence/occurrence.…”
Section: Discussionmentioning
confidence: 98%
“…WBC count is a marker of inflammation, and NLR may be used to predict the prognosis of patients with systemic inflammatory diseases [25][26][27]. Gary et al investigated NLR and its association with critical limb ischemia (CLI) in patients with peripheral arterial occlusive disease (PAOD) [28].…”
Section: Discussionmentioning
confidence: 99%